2012
DOI: 10.1016/j.jcrs.2011.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Corneal deformation signal waveform analysis in keratoconic versus post-femtosecond laser in situ keratomileusis eyes after statistical correction for potentially confounding factors

Abstract: Differences in multiple biomechanical waveform parameters between the keratoconus and post-LASIK groups suggests that waveform analysis may be useful to differentiate between healthy and diseased biomechanical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Detailed explanations of each CDSW parameter have been described before 27. We found higher aindex, p1area, dive2 and mslew2 values in the acromegaly group.…”
Section: Discussionsupporting
confidence: 52%
“…Detailed explanations of each CDSW parameter have been described before 27. We found higher aindex, p1area, dive2 and mslew2 values in the acromegaly group.…”
Section: Discussionsupporting
confidence: 52%
“…Among them, corneal hysteresis (CH) and corneal resistance factor (CRF) have been investigated extensively in different patient groups [12], [13], [14]. These measures provide qualitative information about the biomechanical state of the cornea and additional waveform analysis has been investigated [15], [16], [17]. CoST also uses an air-puff to deform the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analysed multiple biomechanical waveform parameters obtained by ORA and found that six waveform parameters were more useful to distinguish postfemtosecond eyes from keratoconic eyes 14. Several other studies analysed signal waveform of corneal deformation measured using ORA 15 16.…”
Section: Discussionmentioning
confidence: 99%